peran lingkungan sosial dalam memperoleh bahasa kedua prespektif psiko-sosiolingustik - Hendra Gunawan; Riadi Banjarnaor; Muhammad Rifaldi; M Akil Fathur Rahman Syah; Aprijon Efendi (Journal of Innovative and Creativity, 2025)
This study discusses the role of social environment in second language acquisition through a psycho-sociolinguistic approach. Second language acquisition is not only influenced by individual cognitive factors, but is also highly determined by the social context in which individuals interact. This article highlights how factors such as social interaction, motivation, social identity, and attitudes towards a second language shape the process of learning and language mastery. By combining theories from psychology and sociolinguistics, this article emphasizes the importance of the role of family, peers, communities, and educational institutions in creating a supportive environment. The results of the study show that a social environment rich in interaction and supports the active use of a second language can accelerate and deepen language acquisition. These findings provide important implications for the development of second language learning strategies that are more contextual and centered on social interaction.